Meta-analysis of 87Sr/86Sr ratios in otoliths to establish thresholds for determining fish movement - Fábio Ricardo da Rosa; Esteban Avigliano; Fabrice Duponchelle; Luciana Alves Pereira; Marília Hauser; Lorenzo Soriano Antonaccio Barroco; Carlos Edwar de Carvalho Freitas; Raniere Garcez Costa Sousa (Boletim do Instituto de Pesca)
Unpublished data were combined with a literature review to test a hypothesis of whether there is a pattern for classifying fish as “movers” or “residents” according to variability in strontium isotope ( 87 Sr/ 86 Sr) ratios in otoliths as a function of its environmental fingerprint. The variability in Sr ratios found in the otoliths of fish specimens as a percentage of isotopic environmental variability was used to determine the intensity of movement in a given study area (POEVSri index). A classic meta-analysis and a frequentist regression were applied to obtain a logistic model to describe the pattern. The meta-analysis returned a POEVSri limit of 28.95% for sedentary individuals and the logistic model shows a high probability of movement for POEVSri indices over 32%. There is a gradient of movement probabilities in the POEVSri interval from 8 to 32%, with each class having equal odds when POEVSri is approximately 20%. Regarding applicability for future studies, if aspects such as sufficient spatial and seasonal water sampling are addressed, the model provides two different thresholds for fish: a priori “movers” are those with POEVSri ≥ 32%, and resident fish have POEVSri ≤ 8%.